Beyond the state and politics: about the Paris Commune - Barsotti, Paulo (Pontifícia Universidade Católica de São Paulo, 2011)
Since Bakunin and the debate he gave rise towithin the International Workers’ Association, tothe formulations that, inspired by neoliberalism,see in the bloated Stalinist state the materializationof Marxian thought, there is a recurrent idea that Marx defended bureaucracy, politics and the state.Based on various writings by Marx, especially onthe Paris Commune, this article attempts to refutethose accusations.